Exploring the Antibiotic Resistance Profile of Clinical Klebsiella pneumoniae Isolates in Portugal - Ricardo Oliveira; Joana Castro; Sónia Silva; Hugo Oliveira; Maria José Saavedra; Nuno Filipe Azevedo; Carina Almeida (MDPI AG, 2022)
While antibiotic resistance is rising to dangerously high levels, resistance mechanisms are spreading globally among diverse bacterial species. The emergence of antibiotic-resistant Klebsiella pneumoniae, mainly due to the production of antibiotic-inactivating enzymes, is currently responsible for most treatment failures, threatening the effectiveness of classes of antibiotics used for decades. This study assessed the presence of genetic determinants of β-lactam resistance in 102 multi-drug resistant (MDR) K. pneumoniae isolates from patients admitted to two central hospitals in northern Portugal from 2010 to 2020. Antimicrobial susceptibility testing revealed a high rate (>90%) of resistance to most β-lactam antibiotics, except for carbapenems and cephamycins, which showed antimicrobial susceptibility rates in the range of 23.5-34.3% and 40.2-68.6%, respectively. A diverse pool of β-lactam resistance genetic determinants, including carbapenemases- (i.e., blaKPC-like and blaOXA-48-like), extended-spectrum β-lactamases (ESBL; i.e., blaTEM-like, blaCTX-M-like and blaSHV-like), and AmpC β-lactamases-coding genes (i.e., blaCMY-2-like and blaDHA-like) were found in most K. pneumoniae isolates. blaKPC-like (72.5%) and ESBL genes (37.3-74.5%) were the most detected, with approximately 80% of K. pneumoniae isolates presenting two or more resistance genes. As the optimal treatment of β-lactamase-producing K. pneumoniae infections remains problematic, the high co-occurrence of multiple β-lactam resistance genes must be seen as a serious warning of the problem of antimicrobial resistance.